The perceived mental image of a tourist destination based on social media content: An analytical study of Instagram followers' comments on the pages (Sulaymaniyah City, Ain Duhok) - Saeed, Asst.Prof.Dr.Lana Saber Mohammed Saeed (Sulaimani Journal for Humanities, 2025)
A positive and strong image of a tourist destination is a major draw for other tourists. Instagram has become a significant social media platform for promoting tourist destinations, and the comments accompanying promotional posts often play a major role in shaping a positive or negative mental image of the destination. This depends on the follower's experience, which they express in their comments, and these comments indirectly influence the reader's perception of the destination. Therefore, the aim of this study is to understand the nature of the perceived tourist image of the Kurdistan Region's governorates as formed by tourists and reflected in comments on Instagram, with a focus on comments from followers of the Sulaimaniyah and Ain pages. Duhok), and the survey method was adopted due to its methodological and procedural suitability for the current research, as it relies on surveying Instagram page posts using content analysis. The research population consisted of the content of posts on non-Kurdish Instagram pages that focus on tourism in the Kurdistan Region of Iraq, along with the comments on those posts. Using a simple random sample, two pages (Sulaimaniyah City and Ain Duhok) were selected. From this sample, a purposive sample of comments on the posts of these two pages was selected for a period of one month, from March 15, 2025, to April 15, 2025, for each page. Within the specified study period, the sample pages published (186) posts, (124) of which were dedicated to the tourism sector. The most important finding of the current research is that The overall perception of tourism in the region is positive. Emotionally, Sulaimaniyah evokes stronger positive feelings in visitors, while Duhok stirs conflicting emotions. Cognitively, followers trust information about Sulaimaniyah more, while trust in information about Duhok is weaker and more divided. Behaviorally, despite the lower emotional and cognitive trust, the Duhok spring enjoys a slightly higher recommendation rate, demonstrating that its natural beauty and features strongly attract visitors.
Keywords: Perceived mental image; tourist destination; Instagram; follower comments; social media